(untitled) (MMIT Proceedings, 2024)
Consumer psychology is a field of study that includes: advertising, psychology and interface of marketing. Works that integrate consumer psychology includes different fields of theory and different approaches, methods to study and practice. This article will give information about how to impact consumer psychology through modern social media, advertising methods, and via marketing communication. Sales and marketing strategies in our days are developing in various ways and in various forms. This article will review Singaporean marketing strategies and provide marketing suggestions on how to impact customer psychology in order to reach a competitive advantage, to attract more customers, improve sales numbers, evaluation of current business environment and others.